Investigation of a Thermoplastic Polymeric Carrier for Bone Tissue Engineering Using Allogeneic Mesenchymal Stem Cells in Granular Scaffolds - Dimitrios Mylonas, DDS, MS;1 Miguel D. Vidal, DDS, MS;2 (Journal of Prosthodontics, 2007)
The purpose of this project was to compare alveolar bone repair by allogeneic mesenchymal stem cells using bioglass or synthetic hydroxyapatite (HA)/tricalcium phosphate (TCP) granular scaffolds delivered in a thermoplastic polymeric carrier.